TL 18086 - Forefoot axial radiographic study for the evaluation of metatarsal head alignment in the coronal plane - Sposeto, Rafael Barban; Fernandes, Tulio Diniz; Sakaki, Marcos Hideyo; Godoy-Santos, Alexandre Leme; Ortiz, Rafael Trevisan; Corsato, Marcos Andrade (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Many authors consider differences in the relative length of metatarsal bones in the axial plane a cause of inadequate load distribution during gait, leading to metatarsalgia. The goal of surgical treatment is to realign the metatarsal formula. However, many studies have shown a 15% metatarsalgia recurrence rate after reconstructing the advocated metatarsal formula in the axial plane, questioning the importance of the alignment of the metatarsal heads in the coronal plane. Objective: To evaluate the alignment pattern of the metatarsal heads in the coronal plane in individuals with and without metatarsalgia. Methods: This cross-sectional study evaluated individuals aged 30 to 65 years, dividing them into 2 groups, one without foot pain, deformities or callosities and another with metatarsalgia between the 2nd, 3rd and 4th metatarsal bones. The individuals were selected according to inclusion and exclusion criteria and were included in the study after signing an informed consent form. After the selection, the subjects underwent one weight-bearing forefoot axial radiograph evaluating the coronal plane to measure the heights of the metatarsal heads and a weight-bearing anteroposterior foot radiograph to determine the length of each ray. Statistical analysis was performed to compare the measurements of the 2 groups. Results: In total, 106 individuals were divided into 2 groups, each comprising 106 feet, and evaluated. In the group with metatarsalgia, 32% patients were men, the mean age was 49.5 years, and 33 feet had hallux valgus. In the group without metatarsalgia, 51% patients were male, and the mean age was 44.6 years. The measured anthropometric variables did not differ significantly between groups. In both groups, the metatarsal heads were distributed in a curved line in the coronal plane, following the formula M1<M2>M3>M4=M5. The distal support of the 1st ray was in a more plantar position in the group of patients with metatarsalgia (p=0.000). Conclusion: The metatarsal heads of the individuals of both groups were aligned in the coronal plane following the formula M1<M2>M3>M4=M5. However, M1, M4 and M5 were at the same height in the group without metatarsalgia, whereas the M1 weight-bearing point was more plantar in the feet of patients with metatarsalgia.